2000
DOI: 10.1063/1.126269
|View full text |Cite
|
Sign up to set email alerts
|

Silver ion implantation in epitaxial La2/3Ca1/3MnO3 thin films: Large temperature coefficient of resistance for bolometric applications

Abstract: Epitaxial films of La2/3Ca1/3MnO3 were successively implanted with 100 and 200 keV silver ions at fluences of 4.5×1015 and 1×1016 ions/cm2, respectively, to achieve a fairly uniform implant distribution. The as-implanted films are insulating and do not show a metal–insulator transition. Postimplantation annealing at 950 °C shows a recovery of the high structural quality of the films, along with an increase in the metal–insulator transition temperature (Tp), magnetoresistance, and the peak temperature coefficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
30
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 20 publications
1
30
1
Order By: Relevance
“…17 Interest in lanthanum manganite has been rekindled in the last few years due to the observation of large magnetoresistance in films deposited by pulsed laser deposition. Thin films of La-Ca-Mn-O, [18][19][20][21] La-Ba-Mn-O, 22 La-(Ca,Pb)-Mn-O, 23 La-Ce-Mn-O, 24 and La-Sr-Mn-O 25 exhibit magnetoresistance in the range of 5%-150%, which is comparable to that obtained in giant magnetoresistance (GMR) metal multilayers. Jin et al and McCormack et al reported 26,27 a "colossal" magnetoresistance of more than 100 000% for epitaxial La-Ca-Mn-O films on LaAlO 3 .…”
Section: Introductionsupporting
confidence: 53%
“…17 Interest in lanthanum manganite has been rekindled in the last few years due to the observation of large magnetoresistance in films deposited by pulsed laser deposition. Thin films of La-Ca-Mn-O, [18][19][20][21] La-Ba-Mn-O, 22 La-(Ca,Pb)-Mn-O, 23 La-Ce-Mn-O, 24 and La-Sr-Mn-O 25 exhibit magnetoresistance in the range of 5%-150%, which is comparable to that obtained in giant magnetoresistance (GMR) metal multilayers. Jin et al and McCormack et al reported 26,27 a "colossal" magnetoresistance of more than 100 000% for epitaxial La-Ca-Mn-O films on LaAlO 3 .…”
Section: Introductionsupporting
confidence: 53%
“…Ag composites Ag is not substituted into main LCMO lattice but remain rather as an additive in the system. (280 K) is comparable to aligned thin films [6,8,15] of LCMO, and to our knowledge is the best one yet obtained for any polycrystalline mangenites. As far fixed temperature and varying field MR is concerned its shape is changed from U type to V type.…”
mentioning
confidence: 54%
“…The former guarantees the above room temperature T MI and the later high MR. The highest TCR values yet obtained were around 20% for Ag implanted LCMO laser ablated thin films [6,8] and 50% for La 2/3 (Ca,Pb) 1/3 MnO 3 single crystals [9]. For polycrystalline LCMO or similar compounds the TCR values yet seen had always been below 10%.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…3 devices using not only manganite films [13][14][15] but also High Tc (HTc) superconductors [16,17]. In this context, understanding the influence of point defects on the physical properties of manganite films has regain importance.…”
mentioning
confidence: 99%